QUALITATIVE AND QUANTITATIVE ANALYSIS OF BIOLOGICALY ACTIVE COMPONENTS IN MIXTURE OF MULTIVITAMIN RAW MATERIAL OF FOLIA URTICAE AND FRUCTUS SORBI (REVIEW) - V. Yu. Zhilkina; I. A. Yefimova; A. I. Marakhova; O. N. Dontsova (Разработка и регистрация лекарственных средств, 2019)
The article presents the chemical composition of medicinal plants the mixture of the multivitamin raw material. The methods of identification biologically active compounds, depending on their nature, such as the qualitative of the reaction, thin layer chromatography, high performance liquid chromatography are considered. Methods of quantitative definition as separate components of a metabolom of folia Urticae and fructus Sorbi, and total content of biologically active connections are given.